1999
DOI: 10.1108/13665629910300496
|View full text |Cite
|
Sign up to set email alerts
|

Blind date: a case study of mentoring as workplace learning

Abstract: This paper reports on a research project undertaken by the author within a major Australian company which utilised mentoring as part of a leadership training program for potential supervisors. Six pairs of mentors and mentees were asked individually about their perceptions of the mentoring process and of the value of their involvement, personally and professionally. Those responsible for the supervision and conduct of the program were also interviewed. Overall it was clear that the mentees believed they were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 1 publication
3
36
0
Order By: Relevance
“…Because relational mentoring facilitates trust, respect, empowerment, and effective communications, high-quality relationships are more likely to benefit receivers than low-quality relationships (Fletcher and Ragins, 2007). This contention is consistent with a finding showing how much protégés can benefit from mentoring is influenced by the development of mentoring relationship based on trust and openness (Dymock, 1999). As hypothesized above, employees' OCB positively relates to the level of benefits they gain from mentoring functions: Employees will perform more OCB when they benefit more in a high-quality mentoring relationship.…”
Section: Moderating Effects Of Relationship Qualitysupporting
confidence: 80%
“…Because relational mentoring facilitates trust, respect, empowerment, and effective communications, high-quality relationships are more likely to benefit receivers than low-quality relationships (Fletcher and Ragins, 2007). This contention is consistent with a finding showing how much protégés can benefit from mentoring is influenced by the development of mentoring relationship based on trust and openness (Dymock, 1999). As hypothesized above, employees' OCB positively relates to the level of benefits they gain from mentoring functions: Employees will perform more OCB when they benefit more in a high-quality mentoring relationship.…”
Section: Moderating Effects Of Relationship Qualitysupporting
confidence: 80%
“…Richard and colleagues (2009) demonstrated, for example, that when higher levels of trust existed between proté-gés and their mentors, protégés had higher levels of organizational commitment and lower intentions to quit. Further, Dymock (1999) demonstrated that trust in mentoring relationships fostered greater transfer of knowledge between the two parties, which is important if the mentor is to provide developmental advice and feedback to shape the protégé's development. One additional reason to expect trust to be associated with development is the close association between trust and adult attachment styles (Harms, in press).…”
Section: Mentor-protégé Trustmentioning
confidence: 99%
“…Whereas a learning theory perspective defines learning as "the process of using a prior interpretation to construe a new or revised interpretation of the meaning of one's experience to guide future action" (Mezirow, 1996, p. 162), interpreting meaning relies upon one's ability to understand one's frame of reference and (Taylor, 2000), in this case, his or her underlying epistemologies. As workplace learning entails, in part, the ability of a "system to sense and interpret its changing environment and to apply this shared knowledge in order to […] develop the capabilities of its people" (Marsick, 1997, p. 2), training mentors to help a company's workers to develop from within and to value the capabilities and efforts of its members enables the type of organizational development synonymous with organizational learning (Dymock, 1999). Finally, another practical implication of this study is the importance of the climate for supporting learning relationships, as evidenced by the support for H2b.…”
Section: Jwl 275mentioning
confidence: 99%